Self-perception of quality of life and practice of physical activity - Santos, Jorge (2021)
Population aging is an increasingly observable fact in several developed countries. In Portugal, the percentage of elderly people is much higher compared to other age groups. We know that this phase of life causes damage at the biological level, psychological and social problems, which means that the quality of life at this age can decrease. Physical activity can be a means of reversing and / or preventing loss of quality of life. This study aims to verify whether elderly people who practice a regular program of formal physical activity have a better perception of their quality of life than non-practicing elderly people. The sample consisted of 64 elderly people (n = 64), residing in Proença-a-Nova in Portugal, divided into two groups, a group of practitioners in elderly programs and another group not practicing formal physical activity. The perception of quality of life was measured using the MOS SF-36v2 questionnaire, while the battery of tests by the Senior Fitness Test by Rikli and Jones (1999; 2001) was used to assess the functional level. The results showed that the perception of quality of life presents few statistically significant differences, with the highest values being that of the group of practitioners. The perception of quality of life reveals a weak correlation with the functional level presented by the two groups. It was concluded that the practice of physical activity does not influence the perception of quality of life, but it has a significant influence on a better functional level.